Children's emotional expressivity and teacher perceptions of social competence: A cross-cultural comparison. (November 2015) - Louie, Jennifer Yu; Wang, Shu-wen; Fung, Joey; Lau, Anna
Previous research suggests that adult perceptions of children's social competence may vary depending on the socialization goals in a given cultural context. There is also ample evidence of cultural differences in values concerning emotional display, with East Asian collectivistic contexts favoring restraint and Western individualistic contexts favoring open expression of internal states. The present study examined an individualistic versus collectivistic comparison in the links between children's emotional expressivity and teacher evaluations of their social competence. A sample of 127 Korean, Asian American (AA) and European American (EA) preschoolers participated in emotion eliciting tasks and were rated by their teachers on three dimensions of social competence (peer acceptance, prosocial behavior, and antisocial behavior). Moderation analyses revealed that for Korean children, sadness and happiness expressivity were associated with higher antisocial behavior scores, but these associations were reversed or not significant for EAs. For AA children, anger display was associated with lower ratings of peer acceptance and prosocial behavior, but this link did not hold for their EA counterparts. Overall, there was some support for the hypotheses that expressivity was related to lower teacher perceptions of child social competence for a collectivistic group (AA and Korean) but not for an individualistic group (EA). Thus, these findings indicate cultural group differences in teacher perceptions and values of children's emotion expressivity.